2020 ESC Guidelines for themanagement of adult congenital heart disease - H. Baumgartner; J De Backer; S. V. Babu-Narayan; W. Budts; M. Chessa; G.-P. Diller; B. Iung; J. Kluin; I. M. Lang; F. Meijboom; P. Moons; B. J.M. Mulder; et al. (Российский кардиологический журнал)
2020 ESC Guidelines for themanagement of adult congenital heart disease